A bimodal transit system for large cities: cost efficiency and environment friendliness. Issue 3 (2nd December 2022) - Luo, Sida; Kang, Liujiang
Abstract : This paper proposes a bimodal urban transit system with point-to-point transit (PPT) services considering the emission. PPT is designated to serve passengers with long travel distances, connecting two transport hubs with few intermediate stops. We focus on the bimodal system of FRT and PPT, formulating the joint design problem as a mixed-integer program through a parsimonious continuum model. The relative location between FRT and PPT stations varies over space, which complicates route choice analysis. We overcome the challenge by approximating the costs to access transit stations at an aggregate origin-destination level. This is validated by Monte Carlo simulation. Our findings show that the proposed system is both more cost-efficient and eco-friendly than the regular system in cities with high travel demand. However, its performance deteriorates as demand drops. Such a demand threshold is systematically examined in cities with different features such as geographical sizes, PPT speed, and income levels.